Modernisasi Alat Utama Sistem Senjata TNI dalam Mendukung Tugas TNI AL - Prasetiyo, Budi; Riesnandar, Edi; Nendya, Bima (Universitas Batanghari Jambi, 2024)
This study analyzes the modernization of TNI AL weaponry systems to support maritime defense tasks in Indonesian jurisdictional waters. Using the Analytic Network Process (ANP) method, the research identifies the challenges and obstacles faced, as well as determining modernization priorities. The ANP results show that modernizing the Indonesian Navy Warship (KRI) is the top priority, followed by the development of Fast Missile Boats (KCR), the modernization of the Maritime Air Defense System, and the procurement of new submarines. Additionally, the Indonesian Navy faces both conventional military threats, such as naval attacks from other countries, and asymmetric threats, including piracy and maritime terrorism. To address these threats, the Indonesian Navy needs to develop advanced technologies, including cyber security and monitoring technologies to prevent illegal activities at sea. The study also finds that modernization efforts face various obstacles, requiring the improvement of maintenance facilities and intensive training. The use of ANP and NVivo helps formulate an effective modernization strategy to enhance operational readiness and the maritime defense capabilities of the Indonesian Navy.